2015
DOI: 10.1186/s40494-015-0063-0
|View full text |Cite
|
Sign up to set email alerts
|

Indoor/outdoor particulate matter concentrations and microbial load in cultural heritage collections

Abstract: Background: Particulate matter, microorganisms in air and environmental conditions present a potential risk to museum collections. There are also limited studies of simultaneous measurements of airborne particles and microorganisms inside museums and the effects of seasonal variations. Therefore, extensive indoor/outdoor measurements of particulate matter mass/number concentrations and viable, cultivable microbial load were performed in two museums and a library in Greece for a period of 2 years at selected ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…The high number of CFU/m 3 for all species in the present study confirms the findings of other researchers that the museum environment is favourable for the growth of microorganisms, ensuring conditions for survival and propagation an environment with high humidity and a nutrients [8], particularly the patrimony objects of textile and leather being a growth supportive substratum for developing moulds and bacteria [9,10]. According to the results of the quantitative analysis the recommended limits have been exceeded in almost all deposits but also in many of the rooms with full visitors access.…”
Section: Variation Of the Microclimate Parameters On The Air Museum Msupporting
confidence: 79%
“…The high number of CFU/m 3 for all species in the present study confirms the findings of other researchers that the museum environment is favourable for the growth of microorganisms, ensuring conditions for survival and propagation an environment with high humidity and a nutrients [8], particularly the patrimony objects of textile and leather being a growth supportive substratum for developing moulds and bacteria [9,10]. According to the results of the quantitative analysis the recommended limits have been exceeded in almost all deposits but also in many of the rooms with full visitors access.…”
Section: Variation Of the Microclimate Parameters On The Air Museum Msupporting
confidence: 79%
“…In these environments, an inappropriate ventilating or air-conditioning systems may cause fluctuations of temperature and relative humidity. If the microclimate parameters are not stable, biological particles can evolve in a potential threat to objects and humans [6][7][8][9][10][11]. The exposure to some microorganisms, in particular Staphylococcus sp., thermophiles actinomycetes or mycetes, such as Aspergillus, Alternaria, Penicillium, Aureobasidium may induce illness as rhinitis, sinusitis, asthma or alveolitis in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, both culture-based methods and DNA-based molecular approaches such as clone library method based on 16S ribosomal DNA/RNA or ITS (Internal transcribed spacer) regions, PCR-DGGE, NGS (Next-Generation Sequencing) have been widely employed on biological identi cation of the airborne microbes in various historical sites [22][23][24]. Previous studies revealed that airborne microbial concentration and community composition varied greatly among heritage sites, particularly for indoor and outdoor of the museums [23,[25][26][27]. Meanwhile, the microbial concentration and community composition in the atmosphere are in uenced by various factors, mainly natural environment variation (e.g.…”
Section: Introductionmentioning
confidence: 99%